Upaya Peningkatan Kemampuan Pemahaman Matematis dan Kerja Sama Siswa Pada Mata Pelajaran Matematika Materi Pecahan Melalui Pendekatan Matematika Realistik Indonesia Di Kelas V SDN 3 Medayu - Shifa Salsabila; Muryaningsih, Sri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to examine the improvement of mathematical understanding and collaboration skills among fifth-grade students at SDN 3 Medayu through the application of the Indonesian Realistic Mathematics Education (PMRI) approach in leaming fractions. The research employed a Classroom Action Research (CAR) design conducted over two cycles, each comprising two sessions. The study was deemed successful if it met the following indicators: at least 75% of students achieved the Minimum Mastery Criterion (KKTP) with a score of 75 or higher, and there was a measurable improvement in students collaboration skills from Cycle I to Cycle II, reaching a